2014
DOI: 10.1016/j.molcel.2013.12.002
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 6 Is a Chromatin-Bound Cofactor for NF-κB-Dependent Gene Expression

Abstract: Given the intimate link between inflammation and dysregulated cell proliferation in cancer, we investigated cytokine-triggered gene expression in different cell cycle stages. Transcriptome analysis revealed that G1 release through cyclin-dependent kinase 6 (CDK6) and CDK4 primes and cooperates with the cytokine-driven gene response. CDK6 physically and functionally interacts with the NF-κB subunit p65 in the nucleus and is found at promoters of many transcriptionally active NF-κB target genes. CDK6 recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
107
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 50 publications
8
107
1
Order By: Relevance
“…7 A subsequent report described CDK6 as a transcriptional coregulator of nuclear factor kB p65. 8 CDK6 appears to have a key role in hematopoietic tumors, where it is frequently upregulated. 5,7 CDK6 has also been shown to be critical in acute myeloid leukemia (AML) and acute lymphoblastic leukemia driven by mixed lineage leukemia fusion proteins.…”
Section: Introductionmentioning
confidence: 99%
“…7 A subsequent report described CDK6 as a transcriptional coregulator of nuclear factor kB p65. 8 CDK6 appears to have a key role in hematopoietic tumors, where it is frequently upregulated. 5,7 CDK6 has also been shown to be critical in acute myeloid leukemia (AML) and acute lymphoblastic leukemia driven by mixed lineage leukemia fusion proteins.…”
Section: Introductionmentioning
confidence: 99%
“…45 Since it has been reported that CDK6 may affect the transcriptional activity of NF-kB by its ability to phosphorylate the p65 subunit at serine 536, 50,51 we considered it interesting to evaluate whether this kinase could influence total levels of WNT5A. To address this issue we treated the cells with a known CDK6 activity inhibitor (PD332991).…”
Section: The Enhanced Activity Of Cdk6 In Pgrn-deficient Lymphoblast mentioning
confidence: 99%
“…NF-kB induces the expression of pro-inflammatory genes. 20,21 Modulation of cell differentiation Despite the high level of homology between CDK4 and CDK6, there is an increasing list of distinct functions reported for CDK6. Among them is the ability of CDK6 to modulate differentiation in specific cell types including murine erythroid leukemia, primary mouse astrocytes, osteoblasts and osteoclasts, thymocytes, neurons, cardiomyocytes and hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%